A Systematic Literature Review: Development of Education for Remote Indigenous Communities of Papua Based on Social Ecology (RE Park's Theory from Chicago) - Laorens Wantik; Bambang Shergi Laksmono; Avelinus Lefaan; Onnie M. Lumintang (Journal on Education, 2024)
Education for remote indigenous communities in Papua faces complex challenges such as geographical barriers, limited infrastructure, and cultural differences. This study uses a Systematic Literature Review (SLR) to analyze the application of RE Park's social ecology theory in Papua’s education, which views human-environment interaction as the basis for contextual education. Findings indicate that appropriate education for indigenous Papuan communities should integrate local knowledge, cultural values, and ecosystem relationships into the curriculum. This approach not only supports students' practical skills but also strengthens the cultural identity and socio-ecological resilience of communities in the face of environmental changes. Additionally, social ecology-based education can promote social justice and reduce the marginalization of indigenous communities in Papua. This study highlights the importance of a social ecology-based education approach that adapts to the socio-cultural context to enhance inclusiveness and relevance in education for remote indigenous communities.